In Their Own Words: Student Perceptions of Restorative Practices. Issue 4 (14th August 2020) - Skrzypek, Candra; Bascug, Erin W; Ball, Annahita; Kim, Wooksoo; Elze, Diane
Abstract: Restorative practices (RPs) are promising nonpunitive approaches to discipline in schools, yet researchers often overlook students' perspectives. The current study used a mixed-methods approach to explore RP Circle experiences of urban, low-income, and predominantly Black middle school students with attention to the diversity of their experiences by grade level, race, and gender. Quantitative results indicated that younger students reported learning about their behavior by participating in RP Circles. In general, boys felt that Circles supported their nonviolent problem-solving skills more than girls did. Black girls were significantly less likely to endorse the effectiveness of RP Circles to help them solve problems without violence and help them learn about their behavior in comparison with girls of other racial or ethnic backgrounds. Qualitative findings highlighted the benefits of RP Circles in promoting communication, expressing thoughts and feelings, pers pective taking, and opportunity for learning. The study highlights the importance of approaching RP from an intersectional lens and integrating youths' perspectives into programming.